ACHIEVEMENT OF THE IMPLEMENTATION OF THE STRATEGIC PLAN FOR LOCAL DEVELOPMENT IN NAKHONPATHOM PROVINCE - Wangprom, Wuthichai (Journal of MCU Nakhondhat, 2023)
The objectives of this research were: 1) to study the achievement of the implementation of the strategic plan 2) to study the problems and obstacles the achievement of the implementation of the strategic plan 3) to study the appropriate approach the achievement of the implementation of the strategic plan for local development in Nakhonpathom Province. This research was qualitative. The study was from key informants such as executives, leader and Government official of Sampran City Municipality, Rai Khing Municipality, Krathum Lom Municipality, Aomyai Subdistrict Municipality consisted of 20 people by purposive sampling. The data collection instrument was interview form. Data were analyzed by using descriptive statistic. The results found that 1) the achievement of the implementation of the strategic for local development in Nakhonpathom Province consisted of the aspect of formulation of plan to operating local development, the aspect of opportunity for the public to participate, the aspect of listening to issues from the public sector, the aspect of worthiness and benefit to people, the aspect of problem solving in the local effectively, the aspect of transparency checking system, the aspect of monitoring and evaluation, and the aspect of the improve evaluation results to solving for development local in the future. 2) the problems and obstacles the achievement of the strategic for local development in Nakhonpathom Province, namely the local development strategic plan in Nakhonpathom Province such as a few public participation, Lacking knowledge, materials, equipment, not satisfy the people, budget not enough, The integration plan not good, the time planning at short notice, and 3) the appropriate approach of the strategic for local development plan in Nakhonpathom Province, including the plan must be consistent with the government policies, emphasis development the quality of life all aspects as proactive planning. To apply of technology at work could solve people problems and given the opportunity to participate and use resources efficiency